2022
DOI: 10.9734/arrb/2022/v37i1230552
|View full text |Cite
|
Sign up to set email alerts
|

Decolourization and Detoxification of Azo Dye, Malachite Green by Pseudomonas monteilii Strain RZT1, a Bacterium Isolated from Textile Wastewater

Abstract: Discharge of textile industrial effluent without proper treatment has become a severe hazard for the animal health and environment worldwide. Therefore, this study was designed to isolate azo dye-degrading bacteria from textile wastewater and evaluate their ability to biodegrade reactive dyes into non-toxic products. The potent bacterial strain which was isolated from textile wastewater was identified as Pseudomonas monteilii strain RZT1 on the basis of 16S rDNA sequence. The isolated bacterial strain exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The fact that these colors cannot be removed from the body through chemical or physical means gave rise to the notion that biological treatment techniques may be used to remove environmental pollutants. Numerous studies have demonstrated that bacteria may remove a range of natural and synthetic colors from anaerobic and aerobic environments by biosorption, bioaccumulation, and biodegradation [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that these colors cannot be removed from the body through chemical or physical means gave rise to the notion that biological treatment techniques may be used to remove environmental pollutants. Numerous studies have demonstrated that bacteria may remove a range of natural and synthetic colors from anaerobic and aerobic environments by biosorption, bioaccumulation, and biodegradation [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%